Exploratory analysis of CD63 and CD203c expression in basophils from hazelnut sensitized and allergic individuals. Issue 1 (December 2016) - Lötzsch, Bianca; Dölle, Sabine; Vieths, Stefan; Worm, Margitta
Abstract Background Sensitization to hazelnut (HN) is frequent and requires clarification to determine whether this sensitization is clinically relevant. The aim of this study was to investigate basophil activation profiles in HN-sensitized and allergic subjects. Methods Basophil activation was determined by flow cytometric analyses of CD63 and CD203c expression using several HN allergen concentrations. Depending on their clinical reaction pattern, an oral allergy symptom group (OAS, n = 20), a systemic reaction group (n = 12) and a sensitized group without clinical symptoms (n = 20) were identified. Additionally, 10 non-allergic and non-sensitized individuals served as controls. Results CD63 and CD203c expression differed between allergic (OAS and systemic group) and sensitized subjects. The HN concentration required to activate 30% of CD203c+ basophils [effective concentration (EC)30] was significantly higher in sensitized versus the allergic group (p = 0.0089). This was more pronounced when the basophil allergen threshold sensitivity (CD-sens) was calculated (CD63: p = 0.018; CD203c: p = 0.009). Conclusion Our data indicate that the basophil activation test may provide information to better distinguish between sensitized and allergic subjects if several allergen concentrations are considered. CD203c expression displayed a better discrimination compared to CD63; therefore, its diagnostic value might be superior compared with CD63.